2000
DOI: 10.1098/rspa.2000.0559
|View full text |Cite
|
Sign up to set email alerts
|

Multipole solution for the macroscopic electromagnetic boundary conditions at a vacuum—dielectric interface

Abstract: Multipole solutions are obtained for the boundary conditions on the macroscopic electromagnetic elds at the surface of a semi-in nite homogeneous medium in a vacuum, which may be anisotropic, magnetic and chiral. The theory is based on the di¬erential forms of Maxwell's equations and is developed within the electric octopole-magnetic quadrupole approximation, since optical e¬ects are known which require this multipole order for their description. To ensure that both spatial invariance and reciprocity (time-rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Equations (9)(10)(11)(12)(13)(14) are the constitutive relations, for E and B fields represented by complex harmonic plane waves in magnetic media, given by multipole theory to electric quadrupole-magnetic dipole order. Note that the above results, and ones that follow, reduce to those for a non-magnetic medium if we set the time-odd tensors α ij , a ijk and G ij equal to zero.…”
Section: Multipole Theorymentioning
confidence: 99%
“…Equations (9)(10)(11)(12)(13)(14) are the constitutive relations, for E and B fields represented by complex harmonic plane waves in magnetic media, given by multipole theory to electric quadrupole-magnetic dipole order. Note that the above results, and ones that follow, reduce to those for a non-magnetic medium if we set the time-odd tensors α ij , a ijk and G ij equal to zero.…”
Section: Multipole Theorymentioning
confidence: 99%
“…To derive the reflection and transmission coefficients, we require that the tangential components E | | and H | | of E and H are continuous across the interface. This boundary condition is valid for most optical materials, excluding however such specific media in which certain electric quadrupole and higher-order multipoles can be excited to generate lower-order multipoles on the material surface [19,20]. We choose the directions of E and H such that for a zero phase shift, the sign of E | | does not change, but the sign of H | | changes upon reflection, as in Fig.…”
Section: Tangential Reflection and Transmission Coefficients For Spatmentioning
confidence: 99%
“…(41) and (42), to electric octopole-magnetic quadrupole order, are defined as [9] A ı = ε 0 δ ı + F ı − 1 12…”
Section: Covariant Formulation Of the Constitutive Relationsmentioning
confidence: 99%
“…Therefore, possible alternative expressions have to be considered. It is shown that a covariant formulation of the auxiliary fields and the constitutive relations leads to origin-independent expressions for the material constants [9,12] that differ from the ones given in Ref. [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation